Linguistic-Stylistic Analysis of German-Language Drama during Education of Future Philologists - Liliya Kozhedub (Pedagogical Discourse, 2013)
The article describes the features of the German-speaking linguistic-stylistic analysis of drama in the making of foreign language competence in reading in future philologists. Special attention is paid to the analysis of the linguistic features of the material and means of fine drama. The objective difficulties of the structural and semantic organization of dramatic texts were clarified to overcome the difficulties of the students in the process of deep and thorough understanding of the ideological and aesthetic value of the literary text. By specific examples studied linguistic-stylistic peculiarities of the German-speaking drama. Covered approaches to the study of a literary text to analyze the linguistic-stylistic means German-dramas and overcome the complexities of subjective senior students in foreign language reading. The prospects of improving the quality of training of future linguists in terms of the reading competence formation were determined.